ASSESSING THE IMPACT OF RUBBER DEVELOPMENT POLICIES ON THE NATIONAL ECONOMY, INTRA-SECTOR DYNAMICS, AND EMPLOYMENT: UTILIZING A COMPUTABLE GENERAL EQUILIBRIUM MODEL APPROACH - Pinitjitsamut, Montchai; Duangmanee, Piamchan (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – This research explores the effects of three rubber development policies on Thailand's economy and employment: increasing import taxes on rubber products, raising the rubber export tariff (CESS), and boosting domestic rubber consumption. The goal is to strengthen the rubber industry's foundation by promoting policies that enhance domestic rubber utilization, expand the rubber processing industry, and support farmer institutions. Methodology – Using a Computable General Equilibrium (CGE) model, the study analyzes the impact of these policies. Expert brainstorming sessions and in-depth interviews provided additional insights, guiding recommendations for government strategies to streamline rubber supply management and support the entire rubber production chain. Results – Key findings include: 1) Raising the rubber export tariff has minimal impact on the overall economy. 2) Mandating 30% domestic rubber utilization leads to modest economic growth and employment increases, despite Thailand's limited production structure. And 3) Increasing tariffs on imported rubber products has significant macroeconomic effects: a 10% tax increase results in 3.63% economic growth (612,707.70 million THB) and a 2.93% price rise. Employment increases by 6.69%, rubber product prices surge by 23.287% to 26.094%, and primary rubber prices rise by 41.091%. Implications – Policy recommendations include: Streamlining national rubber supply management, supporting upstream rubber production and creating value-added products, aligning rubber research with synthetic rubber needs, - enhancing domestic rubber usage and procurement regulations, developing new strategies for rubber growth, promoting the rubber glove industry, and achieving a 40:60 ratio of natural to synthetic rubber within five years, Establishing rubber special economic zones and strengthening farmer institutions and the Rubber Authority of Thailand (RAOT), and addressing low productivity per acre, establishing a central market, and creating an online platform for future rubber trading to boost producers' earnings and global competitiveness. Originality/Value – Implementing a 10% tariff increase on imported rubber products, comprehensive rubber system management, and maintaining a 30% domestic rubber usage rate are crucial. These measures are expected to invigorate the rubber market and enhance producers' earnings, securing a sustainable competitive advantage globally.